Teaching History in the Nutrition career - Cammarota, Adrián (Universidad Nacional del Litoral, 2018)
The purpose of this paper is to describe and reflect on the importance of Social Sciences in the field of Medical Sciences, based on our experience in teaching Argentinean and Latino American History of Health Sciences in the National University of La Matanza, more specifically in the course of studies for a Bachelor Degree in Nutrition. Our work has been improved by the development of health/disease studies along with an incipient process of including social sciences in the training of health professionals.